Art criticism discourse in the linguistic space: cognitive structures of consciousness by A.S. Pashaev - Aishat S., Danieva; Hazret Z., Bagirokov (Kavkazologiya, 2024)
The article analyzes the features of the art criticism discourse of the Honored Artist of the Che-chen Republic A. Sh. Pashayev. The goal is to reveal the specifics of the cognitive-semantic struc-tures of the linguistic consciousness of the artist, presenting the national ethnoculture with the help of surreal symbols. The study reveals the features of self-awareness, worldview and the sys-tem of relationships between a creative personality and the outside world, broadcasting in the Chechen artistic space a new direction for the North Caucasus socio-cultural space - surrealism. It should be emphasized that the ethnocultural consciousness of the artist presents the objectively existing linguistic and creative specificity of the Chechen linguistic culture through surreal sym-bols, conveying the axiology of the ethnic group, which increases interest in national semiotics and deep value messages. The work is carried out at the intersection of linguophilosophy, socio-cognitive science, linguoculturology and intercultural communication. As a research task, the au-thors identified an attempt to analyze the social role of the artist in creative activity, determining the aesthetic meaning and significance of art historical practices.